Editor-in-Chief’s Message Vol.8(1) - Pradhan, Pratima (KEC Journal of Science and Engineering, 2024)
It is my great pleasure to announce the continued publication of OKRP, KJSE (Office of KEC Research and Publication, KEC Journal of Science and Engineering), which has been ongoing since 2013. This engineering journal primarily aims to encourage research by students, teachers, and professionals engaged in engineering both within and beyond Nepal. Although our college has limited collaboration with industrial sectors, we are proud to host a journal focused on academic research. Nevertheless, we welcome innovations from the industrial sector on our platform. To enhance our journal’s reach, we are also pleased to be included in the NEPJOL platform since 2023. As we strive for greater excellence, we hope to inspire more cutting-edge work through student clubs and collaborations with esteemed universities outside Nepal, guided by a dynamic team of faculty members. We encourage students to explore, experiment, and challenge the status quo. Your ideas matter. Engineering for problem-solving and innovation is continuously evolving with new technologies. Despite the challenges posed by limited research and innovation productivity in Nepal, we are committed to overcoming these hurdles. We are delighted to continue the annual publication of this journal, making each volume increasingly rewarding. I would like to express my gratitude to all the contributors and authors of this journal, as well as to the entire OKRP team and the brilliant experts who have supported us in this endeavor. Your work is the cornerstone of our journal, and we are honored to provide this platform. Yours sincerely, Dr. Pratima Pradhan Editor-in-Chief OKRP, KJSE